Skin hyperpigmentation: a rare presenting symptom of nitrous oxide abuse. (2nd June 2020) - Fang, Xiuying; Li, Weishuai; Gao, Han; Ma, Ying; Dong, Xiaoyu; Zheng, Dongming
Abstract: Context: Recreational nitrogen oxide (N2 O) abuse can cause nervous system damage. There was a sharp increase in the number of patients with neurological disorders associated with recreational N2 O use in China, as recreational N2 O use became popular in young people nationwide. Among cases with neurological disorders caused by N2 O abuse, a few showed skin hyperpigmentation, which has rarely been reported. We explored the characteristics of hyperpigmentation in N2 O abusers to draw the attention of clinicians to this rare cutaneous symptom related to N2 O abuse. Methods: We retrospectively collected data of patients with neurological disorders related to recreational N2 O abuse in Shengjing Hospital of China Medical University from January 2014 to June 2019. Detailed clinical data were gathered from patients who manifested skin pigmentation, including the history of N2 O abuse and characteristics of neurological lesions and skin pigmentation. Results: In total, 66 patients (average age: 22.7 ± 4.5 years, 36 males) with neurological disorders due to N2 O abuse were included; four of them (17–23 years old, 1 male) manifested skin hyperpigmentation. The duration of N2 O abuse of the four patients ranged from 2 to 24 months, and they all had peripheral neuropathy; the two patients also had subacute combined degeneration of the spinal cord. One patient exhibited significant hyperpigmentation throughout the body (trunk, limbs, and face), with no abnormalities in cortisol and other biochemical tests. One patient presented with punctuate pigmentation throughout the trunk. Two patients presented with finger skin pigmentation, especially in the distal phalanxes. Pigmentation after N2 O use remitted slowly with vitamin B12 supplementation. Conclusion: Skin hyperpigmentation is a rare symptom in N2 O abusers, which can distribute locally in hands or diffusely throughout the body. Therefore, attention should be paid to a history of N2 O abuse and serum vitamin B12 level should be tested.